Epistemological Reason of Islamic Psychology: Discourse Analysis of the Development of Islamic Psychology Studies in Indonesia - Muskinul Fuad; Lutfi Faishol (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This paper aims to describe the development of Islamic psychology studies in Indonesia and find an epistemological framework developed by Islamic psychology experts in Indonesia. By utilizing the discourse analysis approach, this study has succeeded in showing that the development of Islamic Psychology studies in Indonesia can be said to be quite dynamic and productive. The reviewers and pioneers of discourse on Islamic Psychology, with their differing backgrounds, have sought to lay the epistemological foundation for the development of Islamic Psychology in the country. The development of Islamic psychology has been pursued through two patterns, namely idealistic patterns and pragmatic (realistic) patterns. Epistemologically, the discourse of Islamic Psychology in Indonesia is characterized by three approaches to understanding the human soul, namely the bayani approach; those with thematic interpretations, speculative philosophical-rational approaches, and a sufistic (irfani) approach that look more closely at the problem of the human soul are based on the spiritual experience of Sufism experts. The three approaches are taken to be able to understand the human soul as a whole. Departing from these three approaches, Islamic Psychology experts in Indonesia then succeeded in formulating various methods that can be taken to produce Islamic Psychology studies that are expected to answer the challenges of Muslims in Indonesia. However, the study of Islamic psychology in Indonesia tends to still be dominated by the epistemological style of bayani and irfani. The burhani approach, even though it has been used, but still tends to attempt to formulate philosophical concepts and soar. This approach has not yet been translated into empirical and applicative research methods (tajribi).